The Combined Hip Procedure: Open Reduction Internal Fixation Combined with Total Hip Arthroplasty for the Management of Severe Acetabular Fractures in the Elderly: A Case Report - Pramukti, Rolandi Indra; Chilmi, Mohammad Zaim; Sedar, Jifaldi A.M.D. (Indonesian Hip and Knee Society (IHKS), 2024)
Acetabular fractures in the elderly are marked by many variability in terms of patient and fracture characteristics. Successful outcomes depend on application of highly individualized (tailor made) management principles. The indications and outcomes associated with various management options, including closed treatment, open reduction internal fixation, and direct or staged total hip arthroplasty. Proper initial management choices are critical, as early failures and subsequent salvage surgery can be accompanied with morbidity. Clinical results after ORIF closely follow the quality of articular reduction and the ability to maintain a congruent reduction of the hip joint. Fracture characteristics and ability to achieve anatomic-articular reduction, should be treated with ORIF. However, fracture characteristics predictive, prior to early post-traumatic arthritis should be treated with simultaneous ORIF and THA (Combine Hip Procedure, CHP). The case presented is one referral institutions treatment algorithm and management approach in dr. Soetomo general hospital.